Inter-regional spillovers in Fukuoka Prefecture: Using VAR model - Hiroshi Sakamoto (European Regional Science Association (ERSA), 2011)
This paper examines the question of inter-regional spillovers in Fukuoka Prefecture. Fukuoka Prefecture is located on the west side of Japan, and is near the Korean peninsula. There are two government-designated major cities in Fukuoka Prefecture. One is Fukuoka City, which is the central city in Fukuoka Prefecture. The other is Kitakyushu City, which is a big city with a population of about one million. The relationship between Fukuoka City and Kitakyushu City is not without problems. Because the two cities are independently administered, each government can execute the policy that best suits its own interest. On the other hand, it is important for Fukuoka Prefecture that both cities economy cooperate. We analyze this question within the framework of three or more than three regions vector-autoregressive (VAR) model. To express the economic relationship in this study, Fukuoka Prefecture is divided into Fukuoka City, Kitakyushu City, and the rest of Fukuoka Prefecture. We subject to extensive sensitivity analysis, with particular attention paid to the effects on the results of strong common output movements.
Keywords: 330